Evaluation of the soil quality across various land use systems of Shapa watershed, Omo Gibe river basin, Ethiopia - Markos Mathewos; Yonas Mathewos (Environmental Research Communications)
Understanding how the quality of the soil parameters differ across different land use categories is essential for enhancing soil fertility, productivity, and environmental sustainability. This study evaluated the soil quality in the Shapa watershed under three nearby land use systems: grassland, enset, and maize. For each land use, soil samples were taken from the surface (0–20 cm depth), and 20 soil quality parameters were investigated. The effect of different land uses on soil quality measures was assessed using a one-way analysis of variance (ANOVA). A minimum data set of 10 indicators chosen from physical and chemical factors was used to generate a soil quality index (SQI). With weights generated from Principal Component Analysis (PCA), the SQI was utilized to evaluate the impact of land use categories on soil quality parameters. The outputs showed significant differences in SQI among the different land uses, with key indicators including bulk density, total porosity, pH, percent base saturation (PBS), available phosphorus, organic carbon (OC), and exchangeable Mg ^+2 . The SQI values were 0.61 for enset land, 0.56 for grassland, and 0.51 for the maize field. Enset and grasslands were classified as intermediate soil quality, while the maize field was categorized as low soil quality, highlighting the need for immediate remedial actions to promote sustainable natural resource management. The study suggests that enhancing soil quality in this research watershed might be realized through improved land use practices that consider farmers’ traditional resource management practices.